Encapsulation of cadmium selenide nanocrystals in biocompatible nanotubes: DFT calculations, X-ray diffraction investigations and confocal fluorescence imaging - Calatayud, David G.; Ge, Haobo; Kuganathan, Navaratnarajah; Mirabello, Vincenz; Jacobs, Robert M.J.; Rees, Nicholas H.; Stoppiello, Craig T.; Khlobystov, Andrei N.; Tyrrell, Rex M.; Da Como, Enrico; Pascu, Sofia I. (Wiley, 2018)
The encapsulation of CdSe nanocrystals within singlewalled carbon nanotubes (SWNTs) cavities of varying dimensions at elevated temperatures under strictly air-tight conditions is described for the first time. The structures of CdSe nanocrystals under confinement inside SWNTs was established in a comprehensive study, combining both experimental and DFT level theoretical investigations. The calculated binding energies show that all considered polymorphs (3, 3), (4, 4) and (4,2) may be obtained experimentally. The most thermodynamically stable structure (3:3) is directly compared to the experimentally observed CdSe structures inside carbon nanotubes. The gas-phase density functional theorycalculated energy differences between “free” 3:3 and 4:2 structures (e.g. whereby 3:3 models a novel tubular structure in which both Cd and Se form three coordination as observed experimentally for HgTe inside SWNT and 4:2 is a motif derived from the hexagonal CuI bulk structure in which both Cd and Se form 4 or 2 coordinations) are surprisingly small, only 0.06 eV per formula unit.. X-ray powder diffraction, Raman spectroscopy, High-resolution transmission electron microscopy (HRTEM) and Energy Dispersive X-ray (EDX) analyses led to the full characterization of the SWNTs filled with the CdSe nanocrystals, shedding light on the composition, structure and the electronic interactions of the new nanohybrid materials on an atomic level. A new emerging hybrid nanomaterial, simultaneously filled and beta-D-glucan coated was obtained using pristine nanotubes and bulk CdSe powder as starting materials. This displayed fluorescence in water dispersions and unexpected biocompatibility was found to be mediated by the beta-D-glucan (a biopolymer extracted from barley) with respect to that of the individual inorganic materials components. For the first time, such supramolecular nanostructures are investigated by life-sciences techniques applied to functional nanomaterials characterization opening the doors for future nano-biotechnological applications.